Monolingualism of Characters of the Song «Michelle» by the Beatles as the Reason of the Communicative Collapse in the Lyrical Text. Part I (Proceedings of Southern Federal University. Philology, 2018)
Sergey G. Nikolaev (Rostov-on-Don, Russian Federation)The lyrics of The Beatles’ song ‘Michelle’ (1965) is linguistically scrutinized in regards of various aspects. The analysis involves those cultural circumstances under which the song was created, as well as the track place in the group legacy. As the author states, the major collision is hidden in the general monolingualism of its characters shown through the foreign-language component, though employed as a device displaying their communication collapse.Key words: English-language popular culture of the 1960s, The Beatles’ works, foreign personal name, intratextual foreignisms, ‘foreign French’, communication collapse.DOI 10.23683/1995-0640-2018-3-12-21